Fullmetal alchemist. 13 - Arakawa, Hiromu, 1973- (Viz Media, 2007)
The political power structure of the military may be irreparable shattered when Colonel Mustang confronts Fuhrer President King Bradley with his suspicion that Bradley is a homunculus.